Recruiting older patients with peripheral arterial disease: evaluating challenges and strategies - Brostow, Diana P (Patient Prefer Adherence, 2015)
Peripheral arterial disease (PAD) is a group of syndromes characterized by chronic and progressive atherosclerosis with a high burden of physical disability and cardiovascular morbidity and mortality. Recruiting patients for clinical research is therefore challenging. In this article, we describe and evaluate our methods for recruiting participants for a cross-sectional feasibility study of PAD, nutritional status, and body composition. We used convenience and purposive sampling approaches to identify potential participants. Between May 2012 and April 2013, 1,446 patients were identified, and 165 patients (11.4%) responded to recruitment requests. The final enrollment was 64 participants (64/1,446; 4.4%), and four subjects (6.3%) subsequently withdrew from the study. Recruiting PAD patients presents a variety of challenges, due largely to the burdens of living with coexistent illnesses, and patients’ reluctance or inability to travel for research. In this article, we delineate suggestions for improving the efficacy of recruitment methods in future PAD studies.